From Romanticism to Virtual Reality: Charles Babbage, William Gibson and the Construction of Cyberspace. - Klein, Herbert (Interdisciplinary Humanities)
The article examines the relationship between Romanticism and post modern cyberpunk by looking at the similarities between the invention of all kinds of machines which first imitate and then try to surpass human qualities the creation of imaginary worlds which open up hitherto undreamed of possibilities. It gives an account of Charles Babbage's work and its roots in Romantic thought, and then show how this work is made to expand into a vision which finally culminates in the idea of cyberspace, which then, despite its original conception as a purely rational visualization of data, turns into a realm where inexplicable and irrational forces reign supreme. William Gibson's trilogy does not affirm or even celebrate the technological development that leads to the construction of cyberspace.